THE LIFE CYCLE OF A MOBILE PHONE: MATERIAL CULTURES OF MANUFACTURING AND CONSUMPTION - de Souza e Silva, Adriana; Farman, Jason; de Cunto Bueno, Daniela (AoIR Selected Papers of Internet Research, 2015)
In this paper, we argue that to truly understand mobile culture, researchers must understand the transnational scope of how these devices come into users’ hands in the first place and where they end up when they are sold, used, and discarded. To achieve this goal, we offer a representative case study of the life cycle of generic cell phones in the city of Rio de Janeiro, Brazil. Brazil is the fifth mobile phone market in the world in absolute numbers (ITU, 2014), and therefore significant as a case study. In addition, Brazil is well known for its mobile black market. Cell phones are among the most stolen items in Brazil, and these devices are either resold in the slums (de Souza e Silva, Sutko, Salis, & de Souza e Silva, 2011), or by street vendors downtown Rio. Re-selling and buying stolen cell phones is considered a crime according to the Brazilian Penal Code, and therefore it is extremely difficult to get both quantitative and qualitative data on this topic, since very rarely subjects acknowledge participating in the offense.